Evaluation of lines of phosphorus and potassium by high-resolution continuum source flame atomic absorption spectrometry for liquid fertilizer analysis - Ferreira, Roberta Borges [UNESP]; Oliveira, Silvana Ruella [UNESP]; Franzini, Vanessa Pezza [UNESP]; Virgilio, Alex [UNESP]; Raposo Jr., Jorge Luiz [UNESP]; Neto, José Anchieta Gomes [UNESP] (My University, 2011)
The usefulness of the side pixel registration approach and molecular absorption was investigated for the determination of phosphorus (P) and potassium (K) in liquid fertilizers by highresolution continuum source flame atomic absorption spectrometry. The phosphorus oxide (PO) lines at 246.400 nm, 247.620 nm, 247.780 nm, 324.616 nm, and 327.040 nm were evaluated. The influence of side pixel registration to extend the linear working range was also investigated by measuring at wings (404.402 nm, 404.406 nm, 404.410 nm, 404.418 nm, 404.422 nm and 404.426 nm) of the secondary line for K at 404.414 nm. For the lines 327.040 nm and 404.422 nm, analytical curves in the 100-5000 mg L.1 P and 50-1000 mg L-1 K ranges were obtained with linear correlations better than 0.999 and 0.995, respectively. The proposed method was applied to six liquid fertilizer samples. The found concentrations for K and P were in agreement with those obtained by inductively coupled plasma optical emission spectrometry (ICP-OES), spectrophotometry, and flame atomic emission spectrometry at the 95% confidence level.